2016
DOI: 10.20308/ejpe.35860
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Metaphors Used By High School Students to Describe Physics, Physics Lesson and Physics Teacher

Abstract: The purpose of this study was to describe high school students' "physics", physics lesson" and "physics teacher" conceptions by using metaphors. 313 students participated in the study from different high school types in Siirt, Turkey. A metaphorical perception form constructed by researcher was individually conducted, digitally recorded and analyzed. Codes and conceptual categories were created. The results demonstrate that students describe physics and physics lesson by using content, function, affective and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
1
8
0
1
Order By: Relevance
“…Thus the use of learning models assisted by e-learning has a very good impact on increasing the critical thinking skills of students in physics education study programs in IPBA courses. In connection with the results of this study, Turgut, et al [5], Yalcin, et al [29] and Çetin [30] said that the successful application of learning models assisted by e-learning is because the learning process has been taught in the right pattern and accordance with physics material. Furthermore, previous research conducted [2], which found that (1) Project-based science learning with ICT (E-learning) media had excellent response criteria and results, (2) Project-based science learning with ICT (e-learning) media is very good in providing students as early as possible as their provision to master the melinial world.…”
Section: Fig 2 Student Response Graphsupporting
confidence: 69%
“…Thus the use of learning models assisted by e-learning has a very good impact on increasing the critical thinking skills of students in physics education study programs in IPBA courses. In connection with the results of this study, Turgut, et al [5], Yalcin, et al [29] and Çetin [30] said that the successful application of learning models assisted by e-learning is because the learning process has been taught in the right pattern and accordance with physics material. Furthermore, previous research conducted [2], which found that (1) Project-based science learning with ICT (E-learning) media had excellent response criteria and results, (2) Project-based science learning with ICT (e-learning) media is very good in providing students as early as possible as their provision to master the melinial world.…”
Section: Fig 2 Student Response Graphsupporting
confidence: 69%
“…Overcoming students' anxiety and possible boredom in learning by shifting learning from a teacher-centered learning system to a student centre and providing motivation. How to overcome the anxiety and possible boredom of students' learning by shifting learning from a teacher-centered learning system to a student centre whose pattern is adjusted to the conditions during science learning (Çetin, 2016;Turgut et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A plethoric amount of literature has reassured that physics is commonly perceived as a difficult and demanding subject (Çetin, 2016;Kessels, et al, 2006;Veloo et al, 2015) among students. Along similar lines, physics teachers report their problematic experiences to effectively implement physics teaching.…”
Section: Difficulties Faced By Physics Teachers In Implementing Physimentioning
confidence: 99%